2021
DOI: 10.1002/ptr.7222
|View full text |Cite
|
Sign up to set email alerts
|

Antiinflammatory phytochemicals against virus‐induced hyperinflammatory responses: Scope, rationale, application, and limitations

Abstract: Uncontrolled inflammatory responses or cytokine storm associated with viral infections results in deleterious consequences such as vascular leakage, severe hemorrhage, shock, immune paralysis, multi‐organ failure, and even death. With the emerging new viral infections and lack of effective prophylactic vaccines, evidence‐based complementary strategies that limit viral infection‐mediated hyperinflammatory responses could be a promising approach to limit host tissue injury. The present review emphasizes the pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 183 publications
1
3
0
Order By: Relevance
“…This increase may be attributed to the immune reconstitution inflammatory syndrome (IRIS), which is an inflammatory condition mediated against the presence of microbial antigens [35] . Previous literature is also in agreement [36] , [37] . A recent study by Seddiki et al [38] reported that patients had developed immune reconstitution inflammatory syndrome following ARV therapy.…”
Section: Arv Therapysupporting
confidence: 85%
“…This increase may be attributed to the immune reconstitution inflammatory syndrome (IRIS), which is an inflammatory condition mediated against the presence of microbial antigens [35] . Previous literature is also in agreement [36] , [37] . A recent study by Seddiki et al [38] reported that patients had developed immune reconstitution inflammatory syndrome following ARV therapy.…”
Section: Arv Therapysupporting
confidence: 85%
“…The mechanism through which a polyphenolic-rich diet can be preventive of carcinogenesis through the favorable modulation of microbiota can include the modulation of hormonal regulation, limiting oxidative and inflammatory injury, and maintaining cellular proliferative/apoptotic homeostasis [233]. Although a detailed discussion on the gut microbiota-associated anti-cancer effects of polyphenols is out of the scope of the manuscript, a detailed discussion on the impact of polyphenols on gut microbiota has been reviewed elsewhere [234][235][236][237].…”
Section: Dietary Strategiesmentioning
confidence: 99%
“…Moreover, the aspirin story continues today: it is still currently the most widely used drug worldwide [ 12 ]. With the emerging new viral infections that mediate hyperinflammatory responses, analyzing natural resources, in order to identify new anti-inflammatory compounds that may limit the host tissue injury, may offer alternative therapeutic or preventive solutions [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%